1, 8-Naphthyridine-based molecular clips for off–on fluorescence sensing of Zn2+ in living cells1. Issue 62 (8th July 2015) - Wang, De-Hui; Zhang, Yuan; Gong, Zhe; Sun, Ran; Zhao, De-Zhi; Sun, Chang-Liang
<x xml:space="preserve">Abstract</x> New 1, 8-naphthyridine-based clip-like receptor as "off–on" fluorescent probe was designed and synthesised for selectively sensing Zn2+ in living cells.